Peculiarities of sensory motion reactions by students of KSAPC - Тропин, Юрий; Романенко, Вячеслав; Голоха, Валерий; Алексеева, Ирина; Алексенко, Яна (Slobozhanskyi Herald of Science and Sport, 2018)
Yura Tropin, Vyacheslav Romanenko, Valeriy Goloha, Iryna Aleksieieva & Yana Aleksenko Purpose: to establish the features of the manifestation of sensorimotor reactions by students of various specializations of KSAPC. Material & Methods: analysis of scientific and methodological information, generalization of best practical experience, psychophysiological methods of research, methods of mathematical statistics. 72 first-year students of the KSAPC, engaged in various sports, aged from 17 to 19, took part in the research. Participants were divided into 4 groups of 18 people: 1 – cyclical sports (track and field, cycling, tourism); 2 – complex coordination sports (sports and artistic gymnastics, acrobatics, sports dances); 3 – sports games (football, basketball, volleyball, handball); 4 – martial artists (freestyle and Greco-Roman wrestling, judo, boxing). Athletes were qualified from the 2nd category to the candidate for master of sports. Results: in the course of the study it was determined that the best indicators of sensorimotor reactions were observed among students of martial artists, and then - in representatives of sports games, complex coordination and cyclic sports. The greatest differences from the results of the assessment of the level of sensorimotor reactions of martial artists were marked with cyclical sports (from 6% to 12%), followed by complex coordination sports (from 3% to 6%) and sports games (from 1% to 5%). Conclusions: conducted research confirmed the importance of psychophysiological characteristics of athletes of various sports as success factors.